2007
DOI: 10.1103/physrevd.76.126006
|View full text |Cite
|
Sign up to set email alerts
|

Single spike solutions for strings onS2andS3

Abstract: We study solutions for rigidly rotating strings on a two sphere. Among them we find two limiting cases that have a particular interest, one is the already known giant magnon and the other we call the single spike solution. The limiting behavior of this last solution is a string infinitely wrapped around the equator. It differs from that solution by the existence of a single spike of heightθ that points toward the north pole. We study its properties and compute its energy E and angular momentum J as a function … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
145
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(164 citation statements)
references
References 55 publications
16
145
0
3
Order By: Relevance
“…Recently a new analysis of the class of spiky string appeared, in [25] infinitely wound string solutions with single spikes on S 2 and S 3 were found. It can be shown that these solutions can be found in a certain limit of the parameters of a general rotating rigid string.…”
Section: Introductionmentioning
confidence: 99%
“…Recently a new analysis of the class of spiky string appeared, in [25] infinitely wound string solutions with single spikes on S 2 and S 3 were found. It can be shown that these solutions can be found in a certain limit of the parameters of a general rotating rigid string.…”
Section: Introductionmentioning
confidence: 99%
“…It would be interesting to study the extension to other target space geometries, such as the sphere. Spiky string solutions are known to exist on the sphere [39,45], thus it is very probable that there is an analogous treatment for them. In higher dimensional symmetric spaces, Pohlmeyer reduction results in multi-component generalizations of the sinh-or cosh-Gordon equations.…”
Section: Jhep07(2016)070mentioning
confidence: 99%
“…In particular, our Lagrangian (3.33), being completely analogous to the one given in (2.26) of [9], should lead to the same energy-charge relation for the giant magnon solution with two angular momenta (see also [27,34]). Moreover, the single spike solutions of [41] can be reproduced also from membranes on AdS 4 × S 7 [42]. In addition, one can consider the correspondence between the Neumann and Neumann-Rosochatius integrable systems arising from membranes and the continuous limit of integrable spin chains at the level of actions, as is done in [43].…”
Section: Discussionmentioning
confidence: 99%